Retrograde Acetabular Micro Perforations, for Treatment of Chondral Lesions Grade 1 and 2 in Patients with Femoroacetabular Impingement - Seidel, Daniela; Parodi, Dante (Achievements and Challenges of Medicine and Medical Science Vol. 10, 2025)
Introduction: Acetabular chondral lesions in patients with femoroacetabular impingement are a common finding in surgical procedures. The reported incidence rate ranges from 78% to 97%. At present, arthroscopic management has proven effective in most cases. Poor results of this treatment have been attributed, among other things, to the presence of articular lesions. Several management alternatives have been described; however, most have been devised for the treatment of grade 3 and 4 cartilage injuries. In fact, there are no good alternatives for the treatment of grade 1 and 2 lesions during hip arthroscopy in patients with Femoroacetabular Impingement. Objective: Here, the study presents a new surgical technique of arthroscopic retrograde drilling for the treatment of grade 1 and 2 acetabular chondral lesions in patients with femoroacetabular impingement. Case Presentation: Grade 1 and 2 acetabular chondral lesions were identified during hip arthroscopy in patients with femoroacetabular impingement. Anterior and anterolateral arthroscopic portals were performed. During the inspection of the central compartment, the acetabular labrum and articular cartilage were evaluated. Through anterior and anterolateral arthroscopic portals, acetabular retrograde drilling is performed from the capsular side of the acetabular rim to the cartilage detachment zone without interrupting the continuity of the articular cartilage surface. Conclusion: Acetabular retrograde drilling is a new arthroscopic treatment alternative for acetabular chondral lesions grade 1 and 2 associated with femoroacetabular impingement. It stimulates the arrival of bone marrow precursors to promote the adhesion of detached cartilage to the subchondral bone, without interrupting the indemnity of the articular cartilage surface. It is technically simple, inexpensive, reproducible, and does not interfere with the rehabilitation protocols.